Operating room myths: what is the evidence for common practices. Issue 4 (August 2015) - Pada, Surinder; Perl, Trish M.
Abstract : Purpose of review: In order to ensure patient safety and prevent surgical site infections (SSIs), operating theaters/rooms have evolved into complex, highly technical environments. Prevention of healthcare-associated infections, and strategies to limit patient harm, have gained momentum over the last decade. This article aims to examine and dispute some commonly held beliefs with specific reference to: laminar airflow, noise and operating theater door openings and how these impact SSI. Recent findings: Laminar airflow may not be necessary for prosthetic implant surgery. Some recent data suggest that there may be patient harm. With the development of better surgical techniques and perioperative care, such costly systems may not be needed. Operating rooms with a high number of door openings have also been shown to experience higher SSI rates, as have operating rooms with high noise levels. These may serve as surrogate markers for operating room discipline. Initiatives which target these areas may be worth considering when devising strategies to reduce SSIs. Summary: Improved surveillance systems for SSIs are needed and should include operating theater airflow type. This will allow further analysis of the effect of laminar air flow on SSIs and provide evidence for a decisive recommendation. Cultivating a culture of good operating theater discipline may also reduce SSIs.